Relation between Family Support and Diet Compliance in Diabetes Militus patients - Popy Irawati; Arif Firmansyah (Universitas Muhammadiyah Tangerang, 2020)
Diabetes mellitus is a group of metabolic disorders characterized by an increase in blood glucose levels (hyperglycemia) due to damage to insulin secretion, insulin action or both. Research Objectives To find out the factors related to adherence in running a diet in people with diabetes mellitus in Cipondoh Health Center, Tangerang-Banten City. This type of research is a quantitative study with a descriptive correlation design using a cross sectional design. The population in this study were 86 diabetic patients. The sampling technique chosen by non probability sampling is the selection of samples that are not randomly done. With ConsecutiveSampling techniques. The chi-square test results show p value α 0,01 so Ha is accepted that there is a relationship between Family Support and Diet Compliance in Diabetes Militus patients. The conclusion of this study is the relationship of family support with dietary compliance in patients with diabetes mellitus